2016
DOI: 10.1080/15275922.2016.1163623
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical assessment of trace metal pollution in sediments of the Cochin backwaters

Abstract: The Cochin backwaters are facing widespread environmental pollution because of the release of solid wastes and liquid effluents from industrial, domestic, and agricultural sectors. The waters are contaminated with trace metals due to an inefficient waste disposal system. Here, the potential trace metal enrichment in sediments related to human activities was evaluated using an enrichment factor, contamination factor, geo-accumulation index, and pollution load index. Metal concentration ranges in sediments durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Sediments can be adopted as an efficient indicator for monitoring heavy metal pollution levels and pollution sources in aquatic environments (George et al 2016). Heavy metals do not form a stable system in the environment, they may be released into water columns by physical, chemical and biological processes, which may affect their properties and forms of occurrence and in turn can increase pollution levels of surrounding waters.…”
Section: Introductionmentioning
confidence: 99%
“…Sediments can be adopted as an efficient indicator for monitoring heavy metal pollution levels and pollution sources in aquatic environments (George et al 2016). Heavy metals do not form a stable system in the environment, they may be released into water columns by physical, chemical and biological processes, which may affect their properties and forms of occurrence and in turn can increase pollution levels of surrounding waters.…”
Section: Introductionmentioning
confidence: 99%
“…Elamin et al (2021), observed increased concentration of trace metals in the water and might be due to the large quantities of solid wastes mixed with the wastes of factories, market and industrial wastes that discharge directly or indirectly into the water bodies. The increased levels of dissolved metals noted during non-monsoon seasons (Table 2) can be attributed to their enrichment caused by enhanced evaporation and increased dissolution from bottomcontaminated sediments due to the prevailing higher water column temperature (Rejomon et al 2016). In most of the dissolved trace metal showed significant spatial and seasonal variation (p ≤ 0.05) at Cochin backwaters (Table 1 and 2).…”
Section: Concentration Of Trace Metal In the Samplementioning
confidence: 95%
“…However, dissolved Cr showed a higher value (0.037 ppm) at station 4 of the south estuary when compared to other stations. The increased levels of dissolved metals like Fe, Zn, Cu, Mn and Cd at station 2 (Bolghatty) are probably due to industrial effluent discharges from industries located at Eloor which reaching at this region by tidal currents and freshwater flows through the Periyar River (Rejomon et al 2016, ). 2021 Likewise, the pulsed levels of dissolved metals like Ni and Pb at station 1 of the Bar mouth region might be due to the extensive dredging operations, shipyard and port activities at the nearby region (Robin et al 2012, Anas et al 2015.…”
Section: Concentration Of Trace Metal In the Samplementioning
confidence: 99%
“…The Cochin backwaters form a complex network of shallow brackish water bodies ~ be heavily polluted by metal waste discharges through industrial, agricultural and municipal sources [3,9,10,11,12]. Thanneermukkom bund for the present study (Figure 1).…”
Section: Study Areamentioning
confidence: 99%
“…Marine pollution by trace metals in aquatic ecosystems have emerged as one of the most serious environmental issues of global concern because of its toxicity, persistence, cumulative effect and risk for humans [1,2]. Anthropogenic activities on land release an increasing amount of trace metals in the environment, especially in aquatic ecosystems [3]. Chronic exposure to trace metals in the aquatic environment is a real threat to living organisms [4].…”
Section: Introductionmentioning
confidence: 99%